Manajemen Proyek Online Trading System PT Universal Broker Indonesia - Noerlina, Noerlina; Deliusno, Deliusno; Retdonero, Retdonero; Eryanto, Dennis (Bina Nusantara University, 2008)
The articles purpose was to setting for global project management including determination of project organization, work breakdown structure, network diagram, and project scheduling, whenever in case to avoid the failure of project or minimize the failure and risk of Online Trading System project on PT Universal Broker Indonesia. The research method was literature study by reading books, internet articles, and others references related to subsequent project management and do survey by directly interviewing to those parties whom related to subsequent project. The research result indicates that PT Universal Broker Indonesia's Online Trading System project is executed according to it's schedule and it hits the requirements. By conclusion, good project's planning and controlment start from beginning until the end will assist the project's running to achieve its purpose.